Present Cardiologic Problems in Indonesia - I. S.F. Ranti (Paediatrica Indonesiana, 1974)
The steady increase of the numberof Cardiovascular diseases and theprogresses made in the diagnostic andsurgical procedures intensified theactivities in the field of Cardiology.At the present time these activitieshave grown beyond medical and tech-nicaI aspects, creating a variety ofsocio-economic problems, requiringactive private and governmental par-ticipation and cooperation.